Evaluation of a miniaturised single-stage thermal modulator for comprehensive two-dimensional gas chromatography of petroleum contaminated soils - MR Jacobs; M Edwards; T Górecki; PN Nesterenko; Robert Shellie (2016)
A novel miniaturised single-stage resistively heated thermal modulator was investigated as an alternative to cryogenic modulation for use in comprehensive two-dimensional gas chromatography (GC×GC). The single-stage thermal modulator described herein yielded average retention time relative standard deviations (RSD) of ≤0.2% RSD (first-dimension) and ≤3.4% RSD (second-dimension). The average peak widths generated by the modulator were 72±3ms, and the peak area precision was better than 5.3% RSD for a range of polar and non-polar test analytes. GC×GC analysis can be performed using this modulator without the requirement for cryogenic cooling or additional pressure control modules for flow modulation. The modulator and associated electronics are compact and amenable towards field analysis. The modulator was used for qualitative and quantitative characterisation of petroleum-contaminated soils derived from a sub-Antarctic research station at Macquarie Island. The limit of detection compared to standard 1D GC analysis was improved from 64 to 11mgkg(-1). An automated method of analysing and categorising samples using principal component analysis is presented.